Nurse led educational intervention on the knowledge of management of selected childhood conditions among mothers of under five in tertiary hospitals in Bayelsa state - Forcebray, Ebikienmo; O., Sowunmi Christiana (International Journal of Research in Medical Sciences, 2020)
Background: Infant and child mortality remains a daunting challenge in Nigeria as findings showed inadequacy in knowledge and skills regarding management of selected childhood conditions among mothers. This study assessed a nurse-led educational intervention on management of selected childhood conditions among mothers of under-five in tertiary hospitals in Bayelsa State. Method: Two group pre-test, post-test quasi-experimental design was used for the study. Total enumeration was adopted to include 150 mothers of under-five. Data were collected using a self-developed questionnaire and a checklist pre and post intervention. Two research questions were answered using descriptive statistics of while hypotheses were tested using inferential statistics of t-test at 0.05 level of significance. Results: Findings showed that pre-intervention knowledge was below average in both control (23.19±6.66) and experimental (21.97±7.32) while an improvement was found with the participants’ post-intervention knowledge on the management of selected childhood conditions in the experimental (49.99±5.86) group and not with the control (23.82±6.75) group. No significant difference was found in the pre intervention knowledge (Mean difference=1.22, t(148)=1.01, p=0.103) in the control and experimental group, while a significant difference was reported in the post intervention mean score on knowledge (Mean diff. = 26.17, t(148)=19.45, p=0.000) in the control and experimental group. Conclusion: The nurse-led intervention programme improved knowledge and skills in the management of selected childhood conditions among mothers of under-five. It is recommended that more awareness should be created on the management of selected childhood conditions parameters.